Trends of blood pressure levels and management in Västerbotten County, Sweden, during 1990–2010 - Ng, Nawi (Co-Action Publishing, 2012)
BACKGROUND: Availability of longitudinal data on hypertension and blood pressure levels are important to assess changes over time at the population level. Moreover, detailed information in different population sub-groups is important to understand inequity and social determinants of blood pressure distribution in the population. OBJECTIVES: The objectives of this study are to: (1) describe the trends of population blood pressure levels in men and women between different educational levels and geographic areas in Sweden during 1990–2010; (2) identify prevalences of hypertension, awareness, treatment, and control in the population; and (3) assess the 10-year risk of developing hypertension among individuals with normal and high normal blood pressures. METHODS: This study is based on data from the Västerbotten Intervention Program (VIP) in Västerbotten County, Sweden. The cross-sectional analysis includes 133,082 VIP health examinations among individuals aged 30, 40, 50, and 60 years from 1990 to 2010. The panel analysis includes 34,868 individuals who were re-examined 10 years after the baseline examination. Individuals completed a self-administered health questionnaire that covers demographic and socio-economic information, self-reported health, and lifestyle behaviours. Blood pressure measurement was obtained prior to the questionnaire. In the cross-sectional analysis, trends of blood pressure by sex, and between educational groups and geographic areas are presented. In the panel analysis, the 10-year risk of developing hypertension is estimated using the predicted probability from logistic regression analysis for each sex, controlling for age and educational level. RESULTS: The prevalence of hypertension decreased from 1990 to 2010; from 43.8 to 36.0% (p < 0.001) among men, and 37.6 to 27.5% among women (p < 0.001). Individuals with basic education had a significantly higher prevalence of hypertension compared to those with medium or high education. Although the decreases were observed in all geographic areas, individuals in rural inland areas had a much higher prevalence compared to those who lived in Umeå City. The proportion of hypertensive women who were aware of their hypertension (61.7%) was significantly higher than men (51.6%). About 34% of men and 42% of women with hypertension reported taking blood pressure medication. Over time, awareness and control of hypertension improved (from 46.5% in 1990 to 69% in 2010 and from 30 to 65%, respectively). The gaps between educational groups diminished. This study shows a significantly higher risk of developing hypertension for men and women with high normal blood pressure compared to those with normal blood pressure at baseline in all age cohorts and educational groups. The average risks of developing hypertension among men with high normal blood pressure were 21.5, 45.8, and 56.3% in the 30, 40, and 50-year cohorts, respectively. Corresponding numbers for women were 22.6, 47.4, and 57.9%. CONCLUSIONS: Levels of blood pressure and hypertension decreased significantly among the Västerbotten population in the last 21 years. Hypertension management has improved and there is increased awareness, treatment, and control of blood pressure. Despite these achievements, the persisting social gaps in blood pressure levels and management demand further investigation and action from policy makers. Future research should attempt to identify and address the root causes of these health inequities to ensure better and equal health for the whole population.